How do you simplify and find the excluded value of (6-y)/(y^2-2y-24)?

2 Answers
Jun 13, 2017

factor the denominator then reduce

Explanation:

y^2-2y-24 factors to (y+4)(y-6).
Now factor a -1 out of the numerator 6-y = -1(y-6)

The factored problem is now [-1(y-6)]/[(y+4)(y-6)

reduce to get -1/(y+4)

Jun 13, 2017

= -1/((y + 4))

excluded value when y = -4

Explanation:

(6 - y)/(y^2 - 2 y - 24) = (6 - y)/((y - 6)(y + 4))

= (6 - y)/(-(-y + 6)(y + 4)) = cancel(6 - y)/(-cancel((6 - y))(y + 4))

= 1/(-(y + 4)) = -1/((y + 4))

excluded value when (y + 4) =0 -> y = -4 therefore y = -4